2006
DOI: 10.1073/pnas.0605796103
|View full text |Cite
|
Sign up to set email alerts
|

Temporary loss of perivascular aquaporin-4 in neocortex after transient middle cerebral artery occlusion in mice

Abstract: The aquaporin-4 (AQP4) pool in the perivascular astrocyte membranes has been shown to be critically involved in the formation and dissolution of brain edema. Cerebral edema is a major cause of morbidity and mortality in stroke. It is therefore essential to know whether the perivascular pool of AQP4 is up-or down-regulated after an ischemic insult, because such changes would determine the time course of edema formation. Here we demonstrate by quantitative immunogold cytochemistry that the ischemic striatum and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
129
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 159 publications
(143 citation statements)
references
References 24 publications
13
129
1
Order By: Relevance
“…Up-regulated AQP4 expression was also found in penetrating brain injury in rats (4) and in cortical contusion injury (3). Other studies show reduced AQP4 expression in response to various insults, including transient middle cerebral artery occlusion in rats (20,21) and diffuse (22) and focal (23) head trauma. Notwithstanding some conflicting results in the literature regarding the direction of change in AQP4 expression in various pathologies, it is concluded that brain AQP4 expression is sensitive to many types of insults, which, from the functional data here, translates to altered brain water balance.…”
Section: Discussionmentioning
confidence: 72%
“…Up-regulated AQP4 expression was also found in penetrating brain injury in rats (4) and in cortical contusion injury (3). Other studies show reduced AQP4 expression in response to various insults, including transient middle cerebral artery occlusion in rats (20,21) and diffuse (22) and focal (23) head trauma. Notwithstanding some conflicting results in the literature regarding the direction of change in AQP4 expression in various pathologies, it is concluded that brain AQP4 expression is sensitive to many types of insults, which, from the functional data here, translates to altered brain water balance.…”
Section: Discussionmentioning
confidence: 72%
“…The level of AQP4 in astrocytic endfeet is much depressed following transient ischemia (45,176). The reduction in AQP4 occurs with no concomitant changes in the level of ␣-syntrophin (45).…”
Section: Regulationmentioning
confidence: 91%
“…In other words, astrocytes may acquire barrier function and restrict water exchange between brain and blood, dependent on their complement of AQP4. This finding has direct implications for a number of experimental and clinical conditions that are characterized by a loss of perivascular AQP4, including mesial temporal lobe epilepsy (16), experimental stroke (17), and a model of Alzheimer's disease (18).…”
Section: Discussionmentioning
confidence: 99%